Dysbetalipoproteinemia. Issue 4 (August 2015) - Marais, David
<x xml:space="preserve">Abstract</x> Purpose of review Lipoprotein metabolism and the role of apolipoprotein E in the pathogenesis of dysbetalipoproteinemia. Recent findings Remnant lipoproteins, modulated by lifestyle and genetic factors, are atherogenic. Dysbetalipoproteinemia could be viewed as a monogenic disorder of remnant metabolism. Summary Elevated plasma triglyceride and cholesterol concentrations (mixed hyperlipidemias) are commonly encountered and dysbetaliproteinemia should be considered in this setting. Dysbetalipoproteinemia (remnant clearance disease, Fredrickson type III hyperlipidemia) is an uncommon dyslipoproteinemia related to mutations in apolipoprotein E that disrupt the clearance of remnants of triglyceride-rich lipoproteins; it may be overlooked because xanthomata of the skin and/or tendons occur in a minority of patients. The diagnosis ideally requires the demonstration of remnant lipoprotein accumulation and a genetic cause. Genotyping for apolipoprotein E2 may not prove the diagnosis as it may be associated with low plasma lipid values. The recent association of remnant lipoproteins with atherosclerosis along with many factors that modulate remnant lipoprotein metabolism underscores the importance of recognising dysbetalipoproteinemia as an extreme state of remnant lipoprotein accumulation. Although there may be some differences between remnants in the general population and dysbetalipoproteinemia, it is clear that remnants promote atherosclerosis. Current treatment strategies are adequate but new strategies could also be of benefit in dysbetalipoproteinemia.